The Improvement of Teachers' Digital Competencies through Informal Learning Motivation in the Workplace - Jakaria, Jakaria; Sudiapermana, Elih; Saripah, Iip; Saepudin, Asep; Yahya, Faridah Hanim (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to evaluate the effectiveness of informal learning motivation in the workplace in enhancing teachers' digital competence in the era of the Industrial Revolution 4.0. This informal learning motivation was designed using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The research sample consisted of 30 teachers, including 5 vice principals. The analysis results show that before the implementation of informal learning motivation, around 40% of teachers lacked confidence in using digital technology, and 60% experienced difficulties in using online learning applications. Encouraging informal learning proved to significantly improve teachers’ digital competence, with the average test score increasing from 50% before the intervention to 80% afterward. In addition, 90% of participants felt more confident using digital learning applications, and 85% found this approach highly relevant to their needs. Despite the positive outcomes, challenges included limited time for mastering the material and the need for continued assistance. Therefore, it is recommended to provide ongoing informal support through intensive mentoring, along with periodic evaluations of technology implementation in learning. Teachers were motivated through the use of social media platforms such as YouTube, Pilot AI, and others. This study recommends that schools formulate internal policies that comprehensively support the integration of technology through informal learning approaches to enhance teachers' professionalism in the future.